Coping with stalking among university students - Björklund, K.; Häkkänen-Nyholm, H.; Sheridan, Lorraine; Roberts, K. (Springer, 2010)
The present study examined behavioral coping actions and coping strategies in relation to specifi c contextual factors (e.g., victim-stalker relationship, stalking violence, duration of stalking, and prior victimization) among Finnish university students. Participants completed a stalking survey, also including items concerning coping. Victims of violent stalking threatened the stalker with the use of certain legal actions signifi cantly more compared with victims of nonviolent stalking, but no difference in the actual use of formal help was found. Instead victims of stalking tried to avoid the stalker or turned to friends and family for help. Victim-stalker relationship, stalker violence, and number of stalking episodes had a signifi cant main effect on certain coping strategies (e.g., positive reappraisal, escape- avoidance, and problem-solving), while no interaction effect was found. The findings suggest that knowledge of victim-coping behavior and strategies is crucial for health care and law enforcement professionals when devising appropriate support for victims and developing multidisciplinary approaches. © 2010 Springer Publishing Company.